The Impact of Integrated Ball Training using Plyometric Exercises on Developing Skill Performance for Youth Football Players under 19 Years - Hamza, Berrah (جامعة العربي بن مهيدي أم البواقي - معهد علوم وتقنيات الشاطات البدنية والرياضية, 2024)
The study aims to investigate the impact of an integrated ball training program using plyometric exercises on developing some fundamental skills of football (scoring, long passing, dribbling) among youth football players under 19 years of age in the state of Oum El-Bouaghi. The research was conducted by implementing a training program and controlled tests on a research sample selected by experts in the field, representing two youth teams: "U.S.C" Union Chaouia and "A.S.A" Association Ain M'lila, both competing in the second national division amateurs of the eastern region with 16 teams. The sample was chosen using purposive sampling method to ensure homogeneity and equivalence between the two groups. The experimental approach was followed in the study, using validated skill tests as data collection tools. These tests were conducted before and after applying the integrated ball training program. The collected data were analyzed statistically using IBM SPSS Statistics 20 software. The paired and independent sample t-tests were employed to analyze the obtained results. The results of the study confirmed the hypotheses, demonstrating post-measurement improvement in the experimental group's fundamental skills: scoring, long passing, and dribbling. This improvement was attributed to the implementation of the integrated ball training program using plyometric exercises.
Keywords: التدريبات الرياضية -- التمرينات البليومترية -- التدريب المدمج -- الأداء المهاري -- كرة القدم